Case–control study of the health of those looked after by local authorities. Issue 4 (1st October 2001) - Williams, J; Jackson, S; Maddocks, A; Cheung, W-Y; Love, A; Hutchings, H
Abstract : AIMS: To assess the health needs and provision of health care to school age children in local authority care. METHODS: A total of 142 children aged 5 to 16 in local authority care, and 119 controls matched by age and sex were studied. Main outcome measures were routine health care, physical, emotional, and behavioural health, health threatening and antisocial behaviour, and health promotion. RESULTS: Compared with children at home, those looked after by local authorities were significantly more likely to: experience changes in general practitioner; have incomplete immunisations; receive inadequate dental care; suffer from anxieties and difficulties in interpersonal relationships; wet the bed; smoke; use illegal drugs; and have been cautioned by police or charged with a criminal offence. They also tend to receive less health education. They were significantly more likely to have had a recent hearing or eye sight test, and reported significantly less physical ill health overall. CONCLUSIONS: The overall health care of children who have been established in care for more than six months is significantly worse than for those living in their own homes, particularly with regard to emotional and behavioural health, and health promotion. In contrast to uncontrolled observational studies we have not found evidence of problems with the physical health of these children.